Basic Statistics Relating to the Indian Economy 1950-51 to 1961-62 - Planning Commission (Planning Commission, 1962)
The document outlines the growth of the Indian economy from 1950-51 through 1961-62, providing a comparative analysis across several key economic indicators during the First Five-Year Plan and subsequent periods. It offers insights organized by various segments including agriculture, industry, trade, public finance, and demographics. The document emphasizes the staggering growth of cooperative societies in credit disbursement while also addressing the challenges presented by overdue loans. A call to action is made for the government to construct a comprehensive policy on agricultural mechanization, aiming to enhance productivity and optimize resources in the farming sector. This report serves as a critical tool for stakeholders to reassess and strategize future directions within the cooperative sector.
Statistics and Surveys Division
Statistics and Surveys Division
Keywords: Credit Societies; Non-Credit Institutions; Outstanding Loans; Delinquency Rates; Agricultural Development Initiatives; Growth Indicators; Agricultural Progress; Industrial Growth; Trade Dynamics